0389 Spontaneous Abortion in Flight Attendants. (23rd June 2014) - Grajewski, Barbara; Whelan, Elizabeth; Lawson, Christina; Hein, Misty; Waters, Martha; Anderson, Jeri; MacDonald, Leslie; Mertens, Christopher; Tseng, Chih-Yu; Rick, Cassinelli; Luo, Lian
Abstract : Objectives: Flight attendant occupational exposures include cosmic ionising radiation and circadian disruption. We wanted to determine whether these and other occupational exposures were associated with spontaneous abortion among female flight attendants. Method: Female flight attendants from three US airlines in three cities were interviewed. Company records of over 1.9 million individual flights during the study period were assessed for exposure to galactic cosmic radiation, solar particle event radiation, and circadian disruption. Measures of physical job demands and other occupational factors were obtained from the interview. Cox proportional hazards regression models were adjusted for age, parity, and nonflying status. Results: Among 2273 women interviewed, 840 pregnancies among 673 women met inclusion criteria. There was evidence to suggest that cosmic radiation exposure of 0.1 mGy or more may be associated with increased risk of spontaneous abortion in weeks 9–13 of the first trimester (odds ratio (OR)=1.74; 95% confidence interval (CI) 0.95–3.20). The risk of a first trimester spontaneous abortion was significantly increased with 15 h or more of flying during home base normal sleep hours (OR=1.54; 95% CI 1.07–2.21) and with high physical job demands (OR=2.49; 95% CI 1.49–4.16). Conclusions: Spontaneous abortion was associated with several flight attendant occupational exposures. This is the first report of these associations based on a quantitative assessment of distinct exposures generated from individual flight records.